Low prevalence of cardiac abnormalities in competitive athletes at return-to-play after COVID-19 - Maestrini, V.; Penza, M.; Filomena, D.; Birtolo, L. I.; Monosilio, S.; Lemme, E.; Squeo, M. R.; Mango, R.; Di Gioia, G.; Serdoz, A.; Fiore, R.; Fedele, F.; et al. (Journal of Science and Medicine in Sport, 2023)
Objective: to evaluate the prevalence of cardiac involvement after COVID-19 in competitive athletes at return-to-play (RTP) evaluation, following the recommended Italian protocol including cardiopulmonary exercise test (CPET) and 24-Hour Holter monitoring. Design and methods: this is a single centre observational, cross-sectional study. Since October 2020, all competitive athletes (age= 14 years) evaluated in our Institute after COVID-19, prior RTP were enrolled. The protocol dictated by the Italian governing bodies included: 12-lead ECG, blood test, CPET, 24-h ECG monitoring, spirometry. Cardiovascular Magnetic Resonance (CMR) was performed based on clinical indication. Results 219 consecutive athletes were examined (59% male), age 23 years (IQR 19-27), 21% asymptomatic, 77% mildly symptomatic, 2% with previous pneumonia. The evaluation was performed after a median of 10 (6-17) days from negative SARS-CoV-2 swab. All athletes showed a good exercise capacity at CPET without cardiovascular and respiratory limitations. Uncommon premature ventricular contractions (PVCs) were found in 9.5% (n=21) at CPET/Holter ECG monitoring. Two athletes (0.9%) were diagnosed with acute myocarditis (by CMR) and another one with new pericardial effusion. All the three athletes were temporally restricted from sport participation. Conclusions Myocarditis in competitive athletes screened after COVID-19 resolution was detected in a low minority of the cases (0.9%). However, a non-negligible prevalence of uncommon PVCs (9%) was observed, either at CPET and/or Holter ECG monitoring, including all athletes with COVID-19 related cardiovascular abnormalities.